2006
DOI: 10.1590/s0037-86822006000600003
|View full text |Cite
|
Sign up to set email alerts
|

Formigas como vetores mecânicos de microorganismos no Hospital Escola da Universidade Federal do Triângulo Mineiro

Abstract: The pathogens associated with ants at the teaching hospital of the Federal University of the Triângulo Mineiro, in Uberaba, MG, were studied. Three species of ants were identified: Tapinoma melanocephalum, Pheidole sp and Paratrechina longicornis. The principal microorganisms found were Staphylococcus sp, Gram-positive bacilli, Pseudomonas sp and Micrococcus sp. The results from the collections were analyzed according to the number of colonies and the different microorganisms isolated, using Student's t test. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
26
1
16

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 4 publications
(2 reference statements)
1
26
1
16
Order By: Relevance
“…Fotedar et al 2 showed that flies caught from hospitals had a bacterial load higher than controls caught in a remote residential area. In contrast, Rahuama et al 5 reported that insects from hospitals had a bacterial load similar to those from outdoors suggesting that isolated bacteria of the insects represents the sanitary conditions of the environment. However, insects are very mobile, having access to human feces, garbage, open wounds, and contaminated medical instruments acting as a link between infected and uninfected areas inside a hospital environment or outside.…”
mentioning
confidence: 92%
See 2 more Smart Citations
“…Fotedar et al 2 showed that flies caught from hospitals had a bacterial load higher than controls caught in a remote residential area. In contrast, Rahuama et al 5 reported that insects from hospitals had a bacterial load similar to those from outdoors suggesting that isolated bacteria of the insects represents the sanitary conditions of the environment. However, insects are very mobile, having access to human feces, garbage, open wounds, and contaminated medical instruments acting as a link between infected and uninfected areas inside a hospital environment or outside.…”
mentioning
confidence: 92%
“…Insecta. Public Health.Some non-biting flying insects, particularly the common housefly (Musca domestica), have sporadically been described as possible mechanical vectors of agents of nosocomial infections because they may carry human pathogens and also due to their ubiquity including in the hospital environments 1-4 .In Brazil, there are some reports showing that ants and cockroaches harbor pathogens in hospitals 5,6 , but there is no report on non-biting flying insects. Therefore, our aim was to investigate the presence of potentially pathogenic bacteria on the external surface of flying insects collected inside a Brazilian health care institution.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A possibilidade de as formigas atuarem como vetor mecânico de bactérias em ambiente hospitalar foi inicialmente investigada na Inglaterra (Beatson 1972). Levantamentos da fauna de formigas em hospitais do Brasil demonstram que esses insetos transportam microrganismos patogênicos, alguns resistentes a antibióticos (Moreira et al 2005), representando risco potencial de infecção em hospitais devido à sua grande mobilidade no interior destes ambientes (Fowler et al 1993, Bueno & Fowler 1994, Costa et al 2006.…”
unclassified
“…The presence of these species puts patients at risk of nosocomial infection. and Costa et al 13 also observed these pathogens.…”
mentioning
confidence: 88%